Recent progress on the total synthesis of acetogenins from Annonaceae - Li, Nianguang; Shi, Zhihao; Tang, Yuping; Chen, Jianwei; Li, Xiang (Beilstein Journal of Organic Chemistry, 2008)
An overview of recent progress on the total synthesis of acetogenins from Annonaceae during the past 12 years is provided. These include mono-tetrahydrofurans, adjacent bis-tetrahydrofurans, nonadjacent bis-tetrahydrofurans, tri-tetrahydrofurans, adjacent tetrahydrofuran-tetrahydropyrans, nonadjacent tetrahydrofuran-tetrahydropyrans, mono-tetrahydropyrans, and acetogenins containing only γ-lactone. This review emphasizes only the first total synthesis of molecules of contemporary interest and syntheses that have helped to correct structures. In addition, some significant results on the novel synthesis and structure–activity relationship studies of annonaceous acetogenins are also introduced.
Keywords: annonaceous acetogenins; antitumor; natural product; total synthesis